Discovery of porcine miRNA‐196a/b may influence porcine adipogenesis in longissimus dorsi muscle by miRNA sequencing. (24th October 2016) - Liu, Linqing; Qian, Kun; Wang, Chonglong
Summary: Intramuscular fat (IMF) is one of the fat traits that has economic importance in the pork industry. Longissimus dorsi muscle contains IMF and is suitable for studying adipogenesis. To discover further potential regulatory miRNAs that may influence adipogenesis, we analyzed miRNA in the longissimus dorsi muscle of Yorkshire (YY, lean‐type) and Chinese Wannanhua (WH, fatty) pigs using miRNA sequencing (miRNA‐seq). From this dataset, we identified 598 unique miRNAs comprising 325 pre‐miRNAs and 273 novel pre‐miRNAs through comparison with known miRNAs in miRBase version 21. We found 42 miRNAs including nine up‐ and 33 down‐regulated between the YY and WH pigs. Moreover, we found two miRNAs, miR‐196a/b (miR‐196a, miR‐196b‐5p), that had the highest level of expression in WH pigs, and miR‐196a/b may influence porcine adipogenesis in longissimus dorsi muscle through an adipocytokine signaling pathway.